Effective Ammonia Removal from Hospital Wastewater by Using a Combination of Filtrations and Bio-Adsorbent from Tea Waste - Ariani, Shinta; Nasir, Subriyer; Melwita, Elda (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
Hospital wastewater contains a high concentration of ammonia that exceed the predetermined quality standards and can cause pollution to the environment. Therefore, the treatment of hospital wastewater is required prior to being released to the environment. Effective ammonia removal process has been developed by using a combination of sponge filtration pretreatment, followed by adsorption using activated carbon from waste of tea leaves, and nanofiltration using ceramic membrane as the final process. Experiment results show the highest effectiveness of ammonia removal of 70% by using filtration only. Effectiveness is increases up to 95% by a combination of filtration and adsorption. A maximum effectiveness of 100% is achieved when using a combination of filtration, adsorption, and nanofiltration. This combination produces an optimal condition for the ammonia removal by using 3 L/min flowrate, adsorbent mass 140 g, and operating time 15 minutes at which the ammonia concentration is 0.08 mg/L. This concentration is below the standard of allowable ammonia concentration of 0.1 mg/L.